PERANCANGAN ULANG STASIUN KERJA PENGISIAN KEMASAN PESTISIDA UNTUK MEMPERBAIKI POSTUR KERJA OPERATOR - Suci Permata Sari; Ratna Purwaningsih (Industrial Engineering Online Journal, 2014)
Granula’s products had been the most eminent product from PT Bina Guna Kimiathat used to control pests such as borer leaf , fly leaf ,  leafhopper , worms , and caterpillars which are pests that oftenly found in entire agricultural land in Indonesia. The kind of fact send the group of granula’s products consist of Marshall, Volvran, and Furadan 3GR as the top 3 largest amount of production. The production activities also required the material handling process. That kind of  process triggering the risk of musculoskeletal disorder for it long period of works to fulfill the target. About 60% report had been collected for musculoskeletal disorder issue in every single months. Based on the RULA assessment the highest report for musculoskeletal disorder collected from filling area at scaling activity with final score showed as 6. The repetitive activity with 8 full hours per shift indicated that the condition has to be change soon. The result of  data processing obtained the filling workstation need an action of redesign with the implementation of new flexioforce conveyor scale to replace the old manual digital scale. Using CATIA, redesign of the conveyor and the limit of dimension will be done based on ergonomic fundamental and anthropometry. Lastly evaluation of the new workstation design will be implementing based on the aspects of RULA to present the improvement of the operator’s posture score for the availment of flexiforce conveyor scale with voice ouput.